Irradiated glass and thermoluminescence yield: Dosimetric utility reviewed - Bradley, D. A. *; Khandaker, Mayeen Uddin *; Abdulaziz, A. (Elsevier, 2020)
With numbers of efforts being made towards harnessing the thermoluminescence yield of doped glass media for dosimetric applications, predominantly in the radiotherapeutic regime, review is provided of the background to this, tracing developments leading to the present day. Included are an examination of the relative strengths of the various TLD currently on offer and that of glass fabrications, commercial Ge-doped optical fibre as well as novel fibres fabricated from Ge-doped glass. The demands that modern radiotherapeutic dose delivery systems are placing upon these passive forms of dosimetry are reviewed together with the various responses arising from current efforts. Also reviewed are the basis of the luminescence yield, citing the defect types occurring in silica, even in the absence of extrinsic dopants.